A Study to Assess the Anxiety and Coping Strategies among First-year B.Sc. Nursing Students in Selected Institutes of Navi Mumbai - Powar, Vishal (International Journal of Nursing Research, 2023)
Background: Students are subjected to different kinds of stressors, such as the pressure of academics with an obligation to succeed, an uncertain future, and difficulties of integrating into the system. Aim: A descriptive study was conducted in selected nursing institutes of Maharashtra to assess stress level and coping strategies among nursing students. A total of 100 1st year nursing students participated in the study. Likert scale was used to assess stress level. Results: Results revealed that 4% of the samples had severe anxiety, 40% had moderate anxiety, 48% had mild anxiety, and 8% of samples have no anxiety. Anxiety levels were significantly higher in females in comparison to males (30.79±7.47 vs. 28.65±7.98; P = 0.036). Coping behavior was comparable in females in comparison to males (53.70±4.62 vs. 53.29±4.40; P = 0.768). Conclusion: Strengthening nursing students’ positive coping skills may be helpful for them to effectively deal with various stressors during their educational experiences while maximizing learning. Implementing empirically tested approaches may be useful to prevent the recurrence of stress and lessen its impact such as stress management counseling, counseling programs, establishing peer and family support systems, and formulating hospital policies that will support nursing students.